Tourism policy rhetoric and practice: A methodological approach to exploring the cyprus context - Liasidou, Sotiroula (My University, 2015)
Tourism policy constitutes a complex issue of analysis given the multidimensional nature of the industry. Understanding policy formation in well-established destinations, as in the case of the island of the Republic of Cyprus, can constitute a contextual backdrop to understand the pitfalls to implementing framed strategy. In particular, this article attempts to shed light on the inability of Cyprus Tourism Organisation (CTO) to enforce successfully the "Tourism Strategic Plan 2003-2010." The primary research involves 26 semistructured interviews by elite policy makers of the island. The results suggest that the industry as such struggles with theoretical tensions, and many gaps are created in terms of the implementation.
Keywords: Cyprus; Semistructured interviews; Strategic planning; Tourism policy